2006
DOI: 10.1007/s11916-006-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous allodynia and migraine: Another view

Abstract: The paradigm of early treatment of the migraine attack at mild pain intensity has become one alternative to circumventing the problem of compromised oral absorption of symptomatic drugs due to migraine-induced gastrointestinal dysmotility. Early treatment also has been proposed to be advantageous because most migraineurs could be less responsive to delayed treatment, owing to the development of central sensitization of the trigeminal pain transmission. Ranking the underlying principles, it seems that the impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…• Dahlöf [27] proposed that impaired gastrointestinal absorption, not allodynia, explains triptan nonresponse in late migraine treatment, but his hypothesis does not explain the fi ndings of Burstein and colleagues [24], as most nonresponders in their study received subcutaneous sumatriptan.…”
Section: Allodynia In Chronic (Transformed) Migrainementioning
confidence: 99%
“…• Dahlöf [27] proposed that impaired gastrointestinal absorption, not allodynia, explains triptan nonresponse in late migraine treatment, but his hypothesis does not explain the fi ndings of Burstein and colleagues [24], as most nonresponders in their study received subcutaneous sumatriptan.…”
Section: Allodynia In Chronic (Transformed) Migrainementioning
confidence: 99%
“…A clinic-based study of patients with chronic migraine has shown that these patients exhibit CA not only during acute headaches, but also in between headache exacerbations [8]. It has been suggested that the presence of CA is associated with decreased response to treatment with the 5-HT 1B/1D agonists, known as triptans [6], although this notion has been debated [10].…”
Section: Introductionmentioning
confidence: 99%
“…Allodynia in migraine is the clinical correlate of central sensitization of neurons in the trigeminal nucleus caudalis [9] . The identification of allodynia in migraine may have therapeutic implications [10], although this notion has been debated [11]. …”
Section: Introductionmentioning
confidence: 99%